IMPLEMENTASI PERATURAN DAERAH KABUPATEN KEBUMEN NOMOR 10 TAHUN 2008 TENTANG PENATAAN PEDAGANG KAKI LIMA DI KABUPATEN KEBUME - Azida Nurul Hayya, Denok Kurniasih dan Dyah Retna Puspita (Universitas Sultan Ageng Tirtayasa, 2017)
Kebumen District Regulation Number 10 Year 2008 on Street Traders tries to organize and manage street hawkers that often disturb the order and beauty around the Kebumen square. The use of square by street hawkers has an adverse impact on the environment. The research was conducted by qualitative research approach, with informant selection using purposive sampling technique to those who are considered competent and representing every element of society related to Implementation of Local Regulation Number 10 Year 2008 on Structuring of Street Traders in Kebumen District. This research gives an overview of research results indicate that implementation can not run well. Implementing the policy can not do much to see from the discretion, initiative and creativity that had been taken. While the impact on the policy objectives has not been able to increase productivity, satisfaction, activity, and compliance of traders. The results of the research can be an input for local government to stop or terminate policy change on Local Regulation No. 10 Year 2008 on the arrangement of street hawkers to be relevant to the conditions in this field.